0571 Associations Between Sleep Problems and Cardiovascular Disease and All-Cause Mortality in Asthma-COPD Overlap. (25th May 2022) - Luyster, Faith; Scott, Paul; Chasens, Eileen; Imes, Christopher; Jeon, Bomin; Shi, Xiaojun; Strollo, Patrick; Baniak, Lynn
Abstract: Introduction: Sleep problems (i.e., short and long sleep duration and sleep disorders) are common in persons with either asthma or chronic obstructive pulmonary disease (COPD) and have been linked to increased cardiovascular risk and mortality. This study determined whether sleep problems are associated with increased cardiovascular disease (CVD) prevalence and all-cause mortality in adults with asthma-COPD overlap (ACO). Methods: Cross-sectional analysis of the 2007-2012 National Health and Nutrition Examination Survey (NHANES) and 2015 National Death Index. Participants (n=7616) were stratified into four groups, using self-report and spirometry data: asthma (n=483), COPD (n=1006), ACO (n=398), and those without asthma or COPD (controls; n=5729). Sleep duration hours were categorized as short (≤5), normal (6-8), and long (≥9). Self-report of physician diagnosis of a sleep disorder (Yes/No) and cardiovascular disease (angina, congestive heart failure, coronary heart disease, hypertension or myocardial infarction) were collected. Logistic and Cox regression models adjusted for covariates were employed. Results: Prevalence of sleep disorders in ACO (24.7%) was roughly two times higher than rates in the asthma (10.7%) and COPD (13.5%) groups and 5 times higher than controls (4.6%). The ACO group had a higher proportion of short sleepers (27.6%) compared to COPD (19.2%) and controls (11.7%) and higher proportion of long sleepers (6.9%) compared to COPD (5.5%). Short sleepers had higher odds for CVD (OR=1.70, 95% CI, 1.34–2.15) compared to normal sleepers. Relative to ACO with normal sleep, long sleepers in the other groups had lower odds for CVD (all P-values <0.05). Both short and long sleepers in the control (HR=0.19, 95% CI 0.07–0.47, and HR=0.07, 95% CI 0.02–0.35, respectively) or COPD (HR=0.38, 95% C, 0.19–0.77, and HR=0.24, 95% CI 0.12–0.51, respectively) groups had lower hazards of all-cause mortality compared to ACO with normal sleep. The influence of presence of sleep disorders on CVD and mortality did not vary between groups. Conclusion: Associations between sleep duration and increased risk of CVD and all-cause mortality were stronger in ACO as compared to COPD and controls. Persons with ACO may represent a high-risk group that should be targeted for assessment and treatment of sleep problems. Support (If Any):